Design of Behavior-Based Reactive System for Autonomous Stuff-Collecting Mobile Robot - Eddy Wijanto (Techné : Jurnal Ilmiah Elektroteknika, 2022)
Recently, autonomous robots play an important role in many aspects. Autonomous robots help improve efficiency and productivity, further reduce errors, and risk rates. Employee safety in high-risk work environments is also becoming one of the benefits of autonomous robots. When designing an autonomous robot, two paradigms can be implemented, i.e., planning and reactive paradigm. A distinct feature of the reactive paradigm is that all activities are carried out through behavior. The benefits of the reactive paradigm include can be applied in limited inexpensive hardware resources, low complexity, goal convergence, easy adaptation to changing situations, and a completely unfamiliar environment with unpredictable mobile obstacles. In this paper, the behavior-based reactive system of an autonomous mobile robot is designed to collect stuff objects. Negotiators have been proposed to combine several behaviors into a system that can be implemented in a variety of situations and cases. The results show that a negotiator can be implemented to realize a fully autonomous mobile robot based on the behavior of the reactive system.